Climate Smart Agriculture: Building Resilience to Climate Change - Lipper, Leslie; McCarthy, Nancy; Zilberman, David; Asfaw, Solomon; Branca, Giacomo (Natural Resource Management and Policy, 2017)
climate change; food security; agricultural development; adaptation